Testing the Role of the Industrial Sector in Protecting the Iraqi Environment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study of the role of the industrial sector in protecting and testing the Iraqienvironment is one of the important matters and issues in diagnosing the path of theeconomy towards achieving sustainable development. The study shows the negativeeffects of the productive processes that occur in this sector. Our study was based on thehypothesis that "the industrial sector has a weak role in the process of protecting theenvironment in Iraq, and industrial investments have not adopted the environmentaldimension at the level of the environmental problem in their accounts when making theinvestment. Depending on the methodology of descriptive and inductive analysis, througha study of the Iraqi industrial sector And testing its role in protecting the environment,and working on the use of scientific books and statistical publications to achieve the goalof the study and knowing the validity of the hypothesis or not.The study concluded that many Iraqi industries were originally established on the basis oftraditional production and not under the umbrella of a clean environment, and it wasnecessary to strengthen the role of these industries in the economic and environmentalfields. Also, it is necessary to re-evaluate existing industrial projects from anenvironmental point of view, and to introduce environmental feasibility studies formodern industrial investments, and to obligate everyone to the Iraqi environmentaldeterminants, conditions and specifications.